Review on sun tracking technology in solar PV system - Anshul Awasthi; Akash Kumar Shukla; S. R. Murali Manohar; Chandrakant Dondariya; K. N. Shukla; Deepak Porwal; Geetam Richhariya (Energy Reports, 2020)
Solar energy is vast, abundant, cost free, green renewable source of energy. Due to the aforementioned qualities, the world is today researching and exploring the most feasibly optimized way of harnessing this energy and solar tracking system is a result of this quest. This paper begins with a brief introduction to the solar PV cells and the materials used in their construction. It also discusses the types of solar PV systems and types of solar tracking systems. It mainly focuses on the design and performance analysis of the various dual-axis tracking solar systems proposed in recent years. Although the choice on the use of trackers mainly depends upon the physical features of the land but in general this system has proved to be more efficient and advantageous than its single-axis and fixed counterparts.
Keywords: 330; Solar energy; Grid; Solar PV; Standalone; Tracking system